Resisting Brazilian Neofascism Through Drone Imagery in (New) Hegemonic Media: The Case of Petra Costa’s The Edge of Democracy (2019) - Pinto, Paulo (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
In The Edge of Democracy (2019, Brazil), Petra Costa denounces the weakening of democracy and the rise of neofascism in Brazil—a crisis that is difficult to understand, as it is instigated, in part, by local hegemonic mass media vehicles and sophisticated virtual arsenals on social media. This intermedial analysis will focus on the filmmaker's poetic gesture of transforming drone-captured images into a personal, reflexive, and structural gaze at the power relations that permeate the plot— an act of subversion of this military-originating device, whose growing role as a mechanism of resistance will be explored. The study also points out the film's paradoxical trajectory through hegemonic institutions of the moving image—Netflix (new) and The Oscars (traditional)—which resulted in a counter-hegemonic discourse being brought into the mainstream and therefore functioning as an artifact of resistance within the plurimedial cyberwar of information surrounding the Brazilian political crisis.